Geologiczno-inżynierska analiza osuwisk na Górze Chełm koło Myślenic - Koza, Paulina (My University, 2016)
This thesis presents a geological-engineering analysis of landslides on the Mount Chełm near Myślenice. It contains a description of the theoretical issues concerning the mass movements, geological-engineering properties and geological analysis of the studied area. As a part of own work, characteristic of investigated landslides has been done. The results were compared, arranged in tables, diagrams and maps. A detailed analysis of the 9908 landslide has been also made. Deformed surface area was compared to the terrain morphology before activating the landslides, what is represented by 3D models, maps and cross-sections. Additionally, a photo documentation has been performed.

Niniejsza praca przedstawia analizę geologiczno–inżynierską osuwisk na Górze Chełm koło Myślenic. Zawiera ona opis teoretyczny dotyczący zagadnienia ruchów masowych, właściwości geologiczno-inżynierskich oraz analizę geologiczną terenu badań. W ramach pracy własnej wykonano charakterystykę badanych osuwisk. Wyniki zostały porównane ze sobą, zestawione w tabelach, diagramach i mapach. Została również wykonana szczegółowa analiza osuwiska 9908. Osunięta powierzchnia terenu została porównana do morfologii terenu przed aktywacją zjawisk osuwiskowych, przedstawiona za pomocą modeli 3D, map i przekrojów. Dodatkowo wykonano dokumentację fotograficzną.
Geological-engineering analysis of landslides on the Mount Chełm near Myślenice
Keywords: analiza geologiczna; osuwisko; morfologia terenu; model 3D; geological-engineering analysis; landslide; terrain morphology; 3D models